2020-2021 Economic Contributions of the Florida Citrus Industry - Julio Cruz; João Pedro Ferreira; Christa Court; Kelsey McDaid (EDIS)
This publication provides a summary of the economic contributions of the citrus industry in the State of Florida during the 2020-2021 citrus marketing year. Additional details on the data sources, methodologies, and results are published in the most recent report on the economic contributions of the citrus industry in Florida from the University of Florida, Institute of Food and Agricultural Sciences (UF/IFAS) Economic Impact Analysis Program. This information is intended to be used in support of informed decision making related to the citrus industry.